Determination of reproducibility of end-exhaled breath-holding in stereotactic body radiation therapy. (15th September 2020) - Sasaki, Motoharu; Ikushima, Hitoshi; Sakuragawa, Kanako; Yokoishi, Michihiro; Tsuzuki, Akira; Sugimoto, Wataru
ABSTRACT: Methods to evaluate the positional reproducibility of breath-hold irradiation mostly require manual operation. The purpose of this study is to propose a method to determine the reproducibility of breath-hold irradiation of lung tumors between fractions using non-artificial methods. This study included 13 patients who underwent terminal exhaled breath-hold irradiation for primary and metastatic lung cancer. All subjects received a prescribed dose of 60 Gy/8 fractions. The contours of the gross tumor volume (GTV) were extracted by threshold processing using treatment-planning computed tomography (CT) and cone-beam CT (CBCT), which was done just before the beginning of the treatment. The method proposed in this study evaluates the dice similarity coefficient (DSC) and Hausdorff distance (HD) by comparing two volumes, the GTVCTS (GTV obtained from treatment-planning CT) and GTVCBCT (GTV obtained from CBCT). The reference contours for DSC and HD are represented by GTVCTS . The results demonstrated good visual agreement for cases with a DSC of ~0.7. However, apparent misalignment occurred when the DSC was <0.5. HD was >2 mm in 3 out of 13 cases, and when the DSC was ~0.7, the HD was ~1 mm. In addition, cases with greater HD also demonstrated more significant variability. It was found that the DSC and HD evaluation methods for the positional reproducibility of breath-hold irradiation proposed in this study are straightforward and can be performed without the involvement of humans. Our study is of extreme significance in the field of radiation studies.